Fictions for the end of the world: a counter-colonial epistemological proposal (PerCursos, 2023)
The end of the world is the horizon that terrifies the world of whiteness. Global collapse has become the quintessential horror, signaling the fading of the future idealized by a humanity shaped by modern-colonial fictions. In this wake, we discuss an epistemological crisis, which, stemming from its narratives born in the cradle of this modern-coloniality, fuels the world we know: the neoliberal-colonial world. In contrast, we propose fictions as a kind of tension against modern epistemologies and, also, as the possibility of writing new epistemologies detached from racist logic. Thus, the end of the world becomes a possibility: for the new to take its place, for History not to reach its end, it is necessary to plot new fictions where this world, in its misery, finds its finitude. Fictions, therefore, as counter-colonial weapons.
Keywords: fictions; counter-colonial epistemology; end of the world